A decentralized open web cryptographic standard. (April 2022) - Das, Dedipyaman; Sethuraman, Sibi Chakkaravarthy; Satapathy, Suresh Chandra
Abstract: Security in web services is not well defined and is largely based on measures employed by the organization providing the service, the effectiveness of which vary greatly depending on the expertise, implementation, and business motivation. To address the mentioned issue, this paper proposes an open standard called Decentralized Open Web Cryptographic Standard (DOWCS) and reference implementation for decentralized protection of sensitive data. Services may adhere to the standards, to assure security to the end-user. Taking OAuth and PGP as reference models, the standard incorporates multiple layers of security to ensure secrecy of the said data while also decentralizing the key information required to derive the confidential data from the encrypted format.